2012
DOI: 10.1126/scitranslmed.3002902
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Consumption Induces Endogenous Opioid Release in the Human Orbitofrontal Cortex and Nucleus Accumbens

Abstract: Excessive consumption of alcohol is among the leading causes of preventable death worldwide. Although ethanol modulates a variety of molecular targets, including several neurotransmitter receptors, the neural mechanisms that underlie its rewarding actions and lead to excessive consumption are unknown. Studies in animals suggest that release of endogenous opioids by ethanol promotes further consumption. To examine this issue in humans and to determine where in the brain endogenous opioids act to promote alcohol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
158
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(165 citation statements)
references
References 55 publications
7
158
0
Order By: Relevance
“…Therefore, antagonism of the higher hypothalamic DRD3 levels resulting in decreased betaendorphin release in the ventral striatum might underpin how DRD3 antagonists impact on addiction. Consistent with this hypothesis, in vivo human PET imaging data have shown that alcohol consumption induces endogenous opioid release in the ventral striatum (Mitchell et al, 2012).…”
Section: D3 Receptors In Alcoholismmentioning
confidence: 75%
“…Therefore, antagonism of the higher hypothalamic DRD3 levels resulting in decreased betaendorphin release in the ventral striatum might underpin how DRD3 antagonists impact on addiction. Consistent with this hypothesis, in vivo human PET imaging data have shown that alcohol consumption induces endogenous opioid release in the ventral striatum (Mitchell et al, 2012).…”
Section: D3 Receptors In Alcoholismmentioning
confidence: 75%
“…The present results join a growing number of studies, indicating that these cortical sites represent crucial loci of clinically relevant opioid action. In humans, ligand PET studies have demonstrated frontal cortical μ-opioid peptide release in association with sweetened-alcohol drinking (Mitchell et al, 2012) and μOR upregulation in frontal sites including the PFC and ACC robustly predicts the severity of craving and rapidity of relapse in cocaine users (Gorelick et al, 2008;Zubieta et al, 1996). μORs are upregulated in the PFC (along with the Acb and amygdala) in individuals with trait impulsivity, and these individuals display exaggerated stressor-induced PFC opioid release (Love et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Endogenous opioids acting at the -opioid receptor (MOR) serve a pivotal function in reward processing and addictive behaviors (Matthes et al, 1996;Hall et al, 2001;Olive et al, 2001;Ghozland et al, 2002;Mathon et al, 2003Mathon et al, , 2005Roth-Deri et al, 2003;Solinas et al, 2004;Jarjour et al, 2009;Mitchell et al, 2012). This is especially the case for MORs regulating the ventral tegmental area (VTA) (Bozarth and Wise, 1984;Wise, 1989;Laviolette et al, 2004), which typically suppress GABAergic inputs to VTA dopamine neurons (Johnson and North, 1992;Manzoni and Williams, 1999;Bergevin et al, 2002;Jalabert et al, 2011;Matsui and Williams, 2011).…”
Section: Introductionmentioning
confidence: 99%